Forsaken relics: practices and rituals of appropriating abandoned artifacts from antiquity to modern times - Buono, Alessandro; Miniaci, Gianluca; Anguissola, Anna (Multidisciplinary approaches to ancient societies (MAtAS), 2024)
Intro -- TOC -- Contributors -- Preface -- Appropriating Places -- Chapter 1: The biographies of Neolithic burnt houses -- Chapter 2: Roman euocatio, or how to get possession of a deserted city -- Chapter 3: Reclaiming the funery space: The protection and re-use of tombs in the burial grounds of Hierapolis in Phrygia -- Redefining Abandonment -- Chapter 4: Relic(t) ecologies. Exploring abandonment in the Apuan Alps -- Chapter 5: Depopulating landscapes: Methodology and the materiality of archives in Calabria -- Chapter 6: Rehabi(li)tating abandonment. Urban occupations and their regenerative practices -- Claiming Things -- Chapter 7: After death: Rituality used to legitimise the appropriation of abandoned goods in ancient Egypt -- Chapter 8: How to preserve an oikos? The case of Isaeus's Oration VIII -- Chapter 9: How to claim things with rites. Care for the dead and inheritance rights in early modern Europe (and beyond) -- Afterword -- Chapter 10: Biographies of place and the significance of place-value.